PENGGUNAAN LAYANAN KONSELING KELOMPOK UNTUK MENINGKATKAN RASA PERCAYA DIRI DALAM BELAJAR - Yondariwati Yondariwati; Yusmansyah Yusmansyah; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to determine the increase in self-confidence in learning after attending a group counseling services in the students. The problem in this study was the low of students’ self-confidence. The question in this study was